INNOVATIVE LOW-RISE HOUSING CONSTRUCTION IN RUSSIA - Krygina, Alevtina Mikhaelovna; Krygina, Natalia Mikhaelovna; Aksenteva, Iuliia Yurevna (Journal of Applied Engineering Science, 2017)
The problem of providing population with affordable and qualitative housing is up-to-datefor Russia. Indicators of housing per person in the Russian Federation are two times lower than European and three times lower than North American. An important problem is high cost of housing services and maintenance. That is whyin modern crisis economic conditions housing inaccessible for some people: for people with low income, pensioners, etc. It forces to look for new campaigns for housing construction. The basic principle of modern housing is to provide rather low construction cost, minimum maintenance expendituresand high ecological rates at all stages of residential real estate life cycle. It can be achieved, first of all, by using energy efficient technologies, building structures and materials with high operational and ecological characteristics. Innovative development concept of low-rise housing construction on the basis of energy saving and ecological approaches is offered. The concept of ecosystem approach realization at all stages of real estate life cycle is developed.
Keywords: Energy efficiency; Innovative eco-real estate; Green building